2012
DOI: 10.1021/bm300103u
|View full text |Cite
|
Sign up to set email alerts
|

Squaric Acid Mediated Synthesis and Biological Activity of a Library of Linear and Hyperbranched Poly(Glycerol)–Protein Conjugates

Abstract: Polymer-protein conjugates generated from side chain functional synthetic polymers are attractive because they can be easily further modified with, for example, labeling groups or targeting ligands. The residue specific modification of proteins with side chain functional synthetic polymers using the traditional coupling strategies may be compromised due to the nonorthogonality of the side-chain and chain-end functional groups of the synthetic polymer, which may lead to side reactions. This study explores the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 43 publications
2
70
0
1
Order By: Relevance
“…A unique benefit of PG is that it carries multiple side-chain hydroxyls, which readily enables further functionalization or architectural variation [25]. A variety of architectures have been demonstrated with PG, including linear, hyperbranched [24], midfunctional, linear-block-hyperbranched [26] and side-chain functional [27]. Klok and coworkers conjugated PG with various architectures to lysozyme through squaric acid diethyl ester mediated coupling to reactive amine groups in the lysine side chains of the protein.…”
Section: Non-degradable Peg Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…A unique benefit of PG is that it carries multiple side-chain hydroxyls, which readily enables further functionalization or architectural variation [25]. A variety of architectures have been demonstrated with PG, including linear, hyperbranched [24], midfunctional, linear-block-hyperbranched [26] and side-chain functional [27]. Klok and coworkers conjugated PG with various architectures to lysozyme through squaric acid diethyl ester mediated coupling to reactive amine groups in the lysine side chains of the protein.…”
Section: Non-degradable Peg Alternativesmentioning
confidence: 99%
“…Klok and coworkers conjugated PG with various architectures to lysozyme through squaric acid diethyl ester mediated coupling to reactive amine groups in the lysine side chains of the protein. A conjugate with midfunctional PG demonstrated significantly higher activity than its linear counterpart at a similar MW [26]. Harth and coworkers were the first to demonstrate in situ grafting of branched PG from Bovine Serum Albumin (BSA) using Ring Opening Polymerization (ROP) with the ability to control the degree of branching [28].…”
Section: Non-degradable Peg Alternativesmentioning
confidence: 99%
“…[ 15 , 18 ] Unfortunately, little systematic modulation of the structure of these polymers has been examined. In a recent study, Wurm et al [ 18 ] have observed only a small effect of polymer architecture on bioactivity within a library of hyperbranched poly(glycerol)-protein conjugates. In their study however, grafting density is quite low and their fi ndings corroborate those herein at low grafting densities.…”
Section: Molecular Sieving For "Smart" Pegylationmentioning
confidence: 99%
“…55 Another interesting class of PEG-like polymers, which, however, so far has been barely explored for the synthesis of protein-polymer conjugates, are polyglycerols (PGs). 56 PGs can be prepared with linear or hyperbranched structures thus providing access to libraries of chemically identical but structurally different polymers for optimizing the pharmacokinetic properties and improving therapeutic effects. 56 In the pursuit for PEG alternatives, oligosaccharides, inspired by the glycosylation of proteins present in nature, have been also considered as PEG analogues.…”
Section: Single Chain Protein Polymer Hybrids For Protein Deliverymentioning
confidence: 99%
“…56 PGs can be prepared with linear or hyperbranched structures thus providing access to libraries of chemically identical but structurally different polymers for optimizing the pharmacokinetic properties and improving therapeutic effects. 56 In the pursuit for PEG alternatives, oligosaccharides, inspired by the glycosylation of proteins present in nature, have been also considered as PEG analogues. 57,58 Likewise, oligosaccharides provide a large hydration shell capable of protecting proteins from proteolysis and introducing prolonged circulation times.…”
Section: Single Chain Protein Polymer Hybrids For Protein Deliverymentioning
confidence: 99%